Inherited human ITK deficiency impairs IFN-γ immunity and underlies tuberculosis (2023)
ABSTRACT: Inborn errors of IFN-γ immunity can underlie tuberculosis (TB). We report three patients from two kindreds without EBV viremia or disease but with severe TB and inherited complete ITK deficiency, a condition associated with severe EBV disease that renders immunological studies challenging. They have CD4+ αβ T lymphocytopenia with a concomitant expansion of CD4-CD8- double-negative (DN) αβ and Vδ2- γδ T lymphocytes, both displaying a unique CD38+CD45RA+T-bet+EOMES- phenotype. Itk-deficient mice recapitulated an expansion of the γδ T and DN αβ T lymphocyte populations in the thymus and spleen, respectively. Moreover, the patients' T lymphocytes secrete small amounts of IFN-γ in response to TCR crosslinking, mitogens, or forced synapse formation with autologous B lymphocytes. Finally, the patients' total lymphocytes secrete small amounts of IFN-γ, and CD4+, CD8+, DN αβ T, Vδ2+ γδ T, and MAIT cells display impaired IFN-γ production in response to BCG. Inherited ITK deficiency undermines the development and function of various IFN-γ-producing T cell subsets, thereby underlying TB.